Development of methods and models to improve the noise immunity of wireless communication channels - Knyazev, Volodymyr; Kravchenko, Vladimir; Lazurenko, Bogdan; Serkov, Oleksandr; Trubchaninova, Karyna; Panchenko, Nataliia (Eastern-European Journal of Enterprise Technologies, 2022)
It has been shown that existing methods and models for improving the noise immunity of communication channels are not capable of meeting requirements for the quality of information in mobile infocommunication systems. In addition, the compromised quality of information fails to protect it and provide the speed of information transmission and density of access channels. It has been proven that reducing the level of electromagnetic radiation is the main method of ensuring noise immunity in wireless mobile communication systems of infocommunication systems. Therefore, one way to ensure the stable interference-free operation is to reduce the level of the information signal at the receiver input to the noise level when the signal/noise ratio is equal to one. This paper reports the results of studying methods and models with correlation reception of ultra-wideband signals. It is proved that according to the level of potential noise immunity, the best indicators are shown by the model of encoding an ultra-wideband information signal by phase manipulation, followed by the coding model with opposite chips, and the code-time manipulation model. It is shown that with a large base of the signal B>300 when the intensity of the received signals is below the level of interference, reliable transmission of information is carried out with a probability of error of less than 10-6. This proves that the use of ultra-wide signal technology allows for wireless hidden transmission of information with low radiation power and a low probability of error. Thus, at a speed of 12 Mb/s, it is possible to chain the transmission of information with a probability of error less than 10-6 if there is a large signal base used, B =500‒1000.